Burnout and resilience in doctors in clinical and preclinical departments in a tertiary care teaching and dedicated COVID-19 hospital - V Pooja (Wolters Kluwer Medknow Publications, 2021)
Background: The worldwide COVID-19 pandemic has significantly altered our life. Doctors more so than the general public because of their involvement in managing the COVID-infected individuals, some of them 24/7 end in burnout. Burnout in doctors can lead to reduced care of patients, increased medical errors, and poor health. Burnout among frontline health-care workers has become a major problem in this ongoing epidemic. On the other hand, doctors in preclinical department have a lack of interaction with patients, with not much nonclinical professional work to boot, find the profession less gratifying which perhaps increase their stress level. Aim: The aim was to study the prevalence of burnout and measure resilience in doctors in clinical and in preclinical departments. Materials and Methods: This observational, cross-sectional, comparative study was carried out in a tertiary care teaching hospital and COVID care center. By purposive sampling 60 preclinical and 60 clinical doctors in a tertiary health care center were included in the study. After obtaining the Institutional Ethics Committee approval and informed consent, the doctors were administered a self made socio-demographic questionnaire, the Copenhagen Burnout Inventory, and the Connor–Davidson Resilience Scale. Doctors were given a self-made questionnaire, the Copenhagen Burnout Inventory, and the Connor–Davidson Resilience Scale. Results: The prevalence of burnout was seen more in clinical doctors (55.47) and the resilience was observed more in preclinical doctors (88.9). Discussion: Resident doctors are a major force to combat COVID-19 as frontline health workers; hence, one can visualize burnout amongst them. On an individual basis, the work-related burnout was severely high in the clinical group owing to the workload which has been corresponding to a number of western studies. Nonclinical department doctors from pathology, community medicine, and microbiology did show burnout but showed a greater score in resilience. Psychological resilience has been identified as a component in preventing burnout. Conclusion: Therapy sessions can be used in clinical doctors facing burnout to build up their resilience.